KEBIJAKAN PENINGKATAN KUALITAS SUMBER DAYA GURU DAN PENGAJARAN SISWA: ANTARA REALITA DAN TUNTUTAN PEMENUHAN INDUSTRI KERJA - Silalahi, Suandi; Fatari, Fatari (Jurnal Bina Bangsa Ekonomika, 2025)
The policy of improving the quality of teachers and student learning is crucial in meeting the demands of the evolving job market. This article explores the challenges, strategies, and initiatives aimed at enhancing the quality of teachers and student learning in Indonesia. From addressing the shortage of qualified teachers to empowering educators to innovate in the classroom, the article emphasizes the importance of continuous professional development, student-centered learning, and community engagement in ensuring high-quality education. By investing in educational resources, aligning the curriculum with industry demands, and implementing data-driven approaches, Indonesia can strive towards a more competitive education system that prepares students for success in the global economy